Assessing Topic Alignment in Pre-tertiary TVET Core Mathematics: A Ghanaian Case Study (2011-2023) - Derick Folson; Francis Kwadwo Awuah (Interdisciplinary Journal of Education, 2025)
Mathematics plays a pivotal role in Technical and Vocational Education and Training (TVET). However, persistent underperformance in the subject limits the academic and career progression of many Ghanaian learners. While various studies have investigated factors influencing achievement, little attention has been paid to the alignment between exit examinations and the curriculum. This study examines the alignment of topics in Ghana’s pre-tertiary TVET Core Mathematics curriculum and exit examinations from 2011 to 2023. Using content analysis and Porter’s alignment model, the study analysed topic distributions in both Paper 1 and Paper 2, computing alignment indices for each year. The results revealed significant variation, with 2017 achieving the highest index (0.807) and 2019 the lowest (0.563). Number and Numeration emerged as the most frequently assessed topic, while areas such as Coordinate Geometry and Trigonometry were minimally represented. Correlation analysis indicated that alignment had a weak, statistically insignificant relationship with learner pass rates. This suggests that while topic alignment is necessary, it alone cannot drive academic success. Other factors. such as instructional quality, resource availability, and cognitive alignment. may also be critical. The study highlights imbalances in topic coverage and misalignment between curriculum intent and assessment practices, offering empirical evidence to inform curriculum and assessment reforms in Ghana’s TVET sector.